Um estudo sobre os sistemas de equações lineares - Silva, Carlos de Abreu Rogério da (2014)
The study of linear equation systems has historically preceded the study of matrixes and determinants. Following this order, we will show that the historical course is viable, and we will give precise significance to the concept of matrix and to the definition of determinant, which have been imprecise and misunderstood due to the order of study. Nowadays almost all of the mathematics high school textbooks which approach this theme have adopted the following order of study: matrixes, determinants, and linear equation systems. This order has made it impracticable for students and teachers to comprehend the concepts of matrix and determinant. This kind of practice has caused enormous damage in the education process of the students. With a simple and objective approach, we introduce in a natural and successive way the concepts of: linear equations, linear equation systems, resolution of linear equation systems, linear system determinant, matrixes, and determinant of matrixes, keeping in mind that matrixes and detetrminants are essential tools for the study and resolution of linear equation systems. We believe that this order of approach can improve the teaching-learning process.